Recoverable room temperature curable reversible material. (December 2020) - Wang, B.; Li, Z.Y.; Xu, J.N.; Liu, F.Y.; Liu, Y.D.
Abstract: Repetitive use and effective recycling of the materials are vital to overcome the current environmental challenges. In case of polymeric materials, the high curing temperatures significantly limit their application. In this study, a series of polymers with thermal reversibility at room temperature were synthesized. The main chain of the polymer systems was composed of polyethylene glycol diglycidyl ether (PEGDGE) and polypropylene glycol diglycidyl ether (PPGDGE). The polymers were obtained by initial chain-extension of furfurylamine (FA) and subsequent Diels-Alder (DA) reaction with bismaleimide (BMI). Fourier transform infrared spectroscopy analysis revealed that the material exhibited fast curing rate and high conversion rate, with the conversion rate reaching 98 %. DSC and DMA characterization demonstrated that the reverse reaction occurred at about 100℃. The tensile analysis confirmed that the mechanical properties of the developed materials remain largely unchanged after recycling, as compared with the existing materials.